THE IMPACT OF PARENTS’ SUPPORT ON STUDENTS’ STUDY HABITS AND ACHIEVEMENT - Yunusova F.B., (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Parental support is widely recognized as a significant factor influencing students’ academic development. This study examines how different forms of parental involvement—such as emotional encouragement, academic guidance, and supervision—affect students’ study habits and overall academic achievement. The research explores how supportive home environments contribute to the development of effective learning behaviors, including time management, consistency, and motivation. It also analyzes the relationship between parental engagement and students’ academic outcomes, highlighting how regular communication, provision of resources, and active interest in education can enhance performance. The findings suggest that students who receive consistent parental support are more likely to demonstrate positive study habits and achieve higher academic results. The study emphasizes the importance of strengthening parent–student relationships to promote better educational outcomes and long-term academic success.